BASIC FEATURES OF LINGUISTIC CHARACTER OF THE WORD MEANING - Majidova Ezozakhon Ibrohim kizi (American Journals Publishing, 2023)
In this article, basic features of linguistic character of the word meaning are analysed. As well as, the article gives a complete description of the meaning of the word, its actualization, the role of context and cites example sentences.
Keywords: pragmatics , context, generative power, linguistic sign, V.V. Vinogradov, G.Leech, precontexts, linguistic units.